How do adolescents classify foods as healthy and unhealthy?: A qualitative inquiry from rural India - Sangeeta Kansal; Aryan Raj; Kumari Smita; Anthony Worsley; Neha Rathi (Journal of Nutritional Science, 2023)
Indian adolescents exhibit obesogenic dietary habits including low intake of fruits and vegetables and increasing consumption of fast food and carbonated beverages. Adolescents’ classification of healthy and unhealthy foods is likely to have significant implications for their dietary behaviour, and consequently, their health. However, there is limited evidence about the ways Indian adolescents classify foods as healthy or unhealthy. Hence, this qualitative study was designed to explore how Indian adolescents classify nutritious or non-nutritious food choices. Convenience sampling was used to recruit the study participants from Tikari village in Uttar Pradesh, India. Underpinned by the social constructivist lens, the adolescents were interviewed face-to-face in Hindi. All the interactions were digitally recorded, transcribed verbatim, and translated into English prior to data analysis. Transcribed data were analysed thematically using inductive as well as deductive coding, and subsequently, conceptual themes were extracted. A total of thirty-nine adolescents (twenty boys; nineteen girls) aged 10–19 years participated in this qualitative inquiry. The adolescents classified healthy and unhealthy foods based on the following six themes: (i) Food groups and nutrients; (ii) Health and immunity; (iii) Type of ingredient; (iv) Place and time of food preparation; (v) Packaging; and (vi) Parental influence. These findings can inform school-based food literacy interventions to foster healthy dietary habits and cooking skills among Indian adolescents.